Composite ink and process for laser-induced selective copper metallization

By using a copper ion and copper oxide composite ink system and optimized process methods, the problems of easy etching of substrates and products during laser-induced metallization, difficulty in preparing high-altitude metal copper products, and high void ratio are solved, and the preparation of metal copper products with high conductivity and low porosity are achieved.

CN118496706BActive Publication Date: 2025-04-08HUAZHONG UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410643703.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2025-04-08
Estimated Expiration
2044-05-23

AI Technical Summary

Technical Problem

During the laser-induced metallization process, existing conductive inks have easy etching of substrates and products, difficult to achieve the preparation of metal copper products with a height of several microns, and high boiling point solvents are prone to microexplosion, resulting in a large number of voids in the metal copper products, affecting their resistivity.

Method used

The copper ion and copper oxide composite ink system is used to fill the gaps between copper oxide particles through copper ion reduction, nucleation, growth and laser-induced melting effect, and optimize the reducing agent and solvent system to remove volatile solvents to avoid micro-explosion.

Benefits of technology

The preparation of metal copper products with high lines, low porosity and high conductivity is achieved, which improves the energy coupling efficiency between laser and matter, reduces the energy penetration of the substrate, and avoids substrate damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118496706B_ABST
    Figure CN118496706B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of selective metallization technology, and in particular to a composite ink and process method for laser-induced selective copper metallization, comprising the following steps: S1, mixing a self-reducing copper salt, a primary amine and a volatile organic solvent to prepare a copper ion ink; S2, mixing the copper ion ink, copper oxide particles and polyvinyl pyrrolidone to prepare a composite ink. The copper ion and copper oxide composite ink system proposed by the present invention fills the gaps between copper oxide nanoparticles through copper ion reduction, nucleation, growth and laser-induced melting effect; the copper element content is greatly increased by the introduction of copper oxide nanoparticles, and finally the preparation of a metallic copper product with high line height, low porosity and high conductivity is achieved; the composite ink system of the present invention can further improve the energy coupling efficiency of laser and matter, improve processing efficiency and avoid damage to the substrate because the copper oxide band gap width matches the wavelength of the mainstream near-infrared laser light source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of selective metallization, and in particular to a composite ink and a process method for laser-induced selective copper metallization. Background Art

[0002] Conductive inks play an important role in the fields of printed electronics, flexible electronics, energy, and medical treatment. Among the existing conductive inks, copper-based conductive inks have attracted much attention due to their excellent conductivity and extremely low cost. However, the inherent oxidation characteristics of copper have imposed many limitations on traditional thermal sintering methods. For this reason, the laser-based non-steady-state induced sintering method has attracted widespread attention from academia and industry due to its advantages of mask-free, high flexibility, high precision, and non-contact. Copper-based inks suitable for laser-induced metallization have also become a research hotspot.

[0003] In existing research, copper-based inks suitable for laser-induced metallization mainly include copper ion inks, copper oxide nanoparticle inks, and copper nanoparticle inks. Although significant research results have been achieved, these technical solutions still have some problems: (1) The optical absorption peaks of existing copper ion inks are located in the ultraviolet band and the 600nm-700nm red light band, which puts forward special requirements for laser light sources and back-end optical components. Ultraviolet lasers require nonlinear frequency doubling, which has low conversion efficiency. In addition, due to the high energy of photons in the ultraviolet band, it is very easy to cause etching of the product and the substrate. The 600nm-700nm red light band lacks mature high-performance laser light sources and back-end beam shaping, focusing and scanning modules. (2) For copper ion inks, due to the low inherent copper content in copper salts and the solubility of organic copper salts in solvents, the copper content of copper-organic decomposition inks is low. In addition, the mass loss of the ink during the decomposition process makes the product thinner, only a few hundred nanometers, making it difficult to prepare metal copper products with a height of several microns, which seriously limits the macroscopic resistance of the product. (3) The existing copper nanoparticle ink is very easy to oxidize during storage and use due to the high activity of nano copper, which makes it more expensive, making the laser-induced metallic copper lose its cost advantage over the conductive silver paste, and the copper surface oxide layer formed seriously affects the conductive properties of the copper film or copper conductive circuit. (4) The existing copper oxide ink mostly relies on ethylene glycol, which is difficult to volatilize, as a reducing agent. Under the action of laser, local high temperature will cause ethylene glycol to boil, resulting in a large number of voids in the product, resulting in a porosity of 10%-30%, resulting in a large number of pores in the product. The resistivity of the product is usually 2 orders of magnitude higher than that of bulk copper, and it has no application prospects. Summary of the invention

[0004] In view of this, the present invention proposes a composite ink and process method for laser-induced selective copper metallization to solve the problems that in the process of preparing metallic copper products by laser direct writing in existing conductive inks, the substrate and the product are easily etched and it is difficult to prepare metallic copper products with a height of several microns. In addition, the high-boiling point solvent in the existing ink composition is prone to micro-explosion under the action of laser, resulting in a large number of voids in the metallic copper product, affecting its resistivity.

[0005] The technical solution of the present invention is achieved in this way:

[0006] In a first aspect, the present invention provides a method for preparing a composite ink for laser-induced selective copper metallization, comprising the following steps:

[0007] S1. Mixing a self-reducible copper salt, a long alkyl primary amine and a volatile organic solvent to prepare a copper ion ink;

[0008] S2. Mix the copper ion ink, copper oxide particles and polyvinyl pyrrolidone to prepare a composite ink.

[0009] In the present invention, in step S1, the self-reducing copper salt is decomposed and reduced to metallic copper under the action of laser, and the long alkyl primary amine is used as a complexing agent to regulate the copper ion reduction nucleation process, so as to make the copper particles smaller and more evenly distributed. In step S2, copper oxide nanoparticles are introduced to be compounded with copper ion ink, and copper ions are reduced to nuclei under the induction of near-infrared laser to produce particles, which are then melted and filled into the pores between copper oxide particles, thereby reducing the porosity of the product and improving the conductivity; at the same time, the copper oxide band gap width (~1.2eV) in the composite ink system matches the wavelength of the near-infrared laser light source (1000nm~1100nm), so there is strong absorption in this wavelength range, which is beneficial to further improve the laser and material energy coupling efficiency, improve processing efficiency, and avoid damage to the substrate. Polyvinyl pyrrolidone is used as a dispersant for copper oxide nanoparticles, and the hydrophilic groups in its molecules are adsorbed on the surface of copper oxide particles, and the hydrophobic groups extend to the solvent. The steric hindrance prevents the particles from agglomerating, which plays a role in dispersion and stabilization. At the same time, under the action of laser, polyvinyl pyrrolidone can be used as a reducing agent for copper oxide particles. Volatile organic solvents as solvents for composite inks can be completely removed by heating before laser processing to avoid micro-explosion of solvents during laser processing and reduce the porosity of the product.

[0010] On the basis of the above technical solution, preferably, the molar ratio of the self-reducible copper salt to the long alkyl primary amine is 1:1.5-2.5, and the copper ion concentration in the copper ion ink is 1-5 mol / L.

[0011] By adjusting the molar ratio of the self-reducing copper salt and the long alkyl primary amine (1:1.5-2.5), the degree of copper ion complexation can be optimized, which can not only ensure sufficient copper source, but also control the reduction nucleation process to obtain a metallic copper product with excellent performance. The copper ion concentration is selected in the range of 1-5 mol / L. A high enough concentration is conducive to improving the deposition rate of metallic copper and the thickness of the product; but the concentration should not be too high, otherwise it will affect the stability and fluidity of the ink.

[0012] On the basis of the above technical scheme, preferably, the self-reducing copper salt includes copper formate or copper glyoxylate, the long alkyl primary amine includes one or more organic primary amines with an alkyl chain length ≥ 5; and the volatile organic solvent includes a volatile alcohol solvent with a boiling point less than or equal to 85°C.

[0013] In the present invention, a long alkyl primary amine with an alkyl chain length of ≥5 is used as a complexing agent. The long alkyl primary amine forms a coordination bond with the copper ion to generate a relatively stable copper-amine complex. The coordination strength is moderate, which can effectively complex the copper ion and is not too stable to be difficult to reduce. The long alkyl chain in the long alkyl primary amine has a steric hindrance effect, which can control the reduction nucleation speed of the copper ion. When the copper ion is reduced, the long chain alkyl forms a protective layer around the copper core, which hinders the further growth of the copper core, thereby obtaining copper nanoparticles with smaller size and more uniform distribution.

[0014] On the basis of the above technical scheme, preferably, the preparation method of the self-reducing copper salt comprises: mixing a copper metal salt solution and a reducing carboxylic acid solution, reacting at 24-28°C for 6-12 hours, removing the solvent to obtain a self-reducing copper salt, and the pH value of the reducing carboxylic acid solution is 6-8.

[0015] Specifically, a copper metal salt is dissolved in deionized water to form a copper metal salt solution, a reducing carboxylic acid is dissolved in deionized water to form a reducing carboxylic acid solution, and a 15wt%-25wt% sodium hydroxide solution is used to adjust the pH value of the reducing carboxylic acid solution to 6-8. The pH value of the reducing carboxylic acid solution is controlled within a neutral range of 6-8. On the one hand, a neutral environment is conducive to the dissolution and reaction of copper salts; on the other hand, too high a pH value will affect the stability of the self-reducing copper salt. On the basis of the above technical scheme, preferably, the concentration of the copper metal salt solution is 0.5-1 mol / L, and the copper metal salt solution includes one or more of a copper sulfate solution, a copper nitrate solution, and a copper chloride solution; the concentration of the reducing carboxylic acid solution is 1-2 mol / L, and the reducing carboxylic acid solution includes a formic acid solution and / or a glyoxylic acid solution.

[0016] Both formic acid and glyoxylic acid are reducing, and the copper salts generated by them and copper ions are self-reducing and can self-decompose under heating conditions to produce metallic copper. Based on the above technical solution, preferably, the copper oxide particles are spherical and / or flaky, and the particle size of the copper oxide particles is 20nm to 2μm.

[0017] Specifically, under near-infrared laser irradiation, copper ions are reduced to nuclei to form nanoscale copper particles, and are filled into the pores between copper oxide particles in a molten state. The ink made of spherical copper oxide nanoparticles has better fluidity, while the flaky copper oxide nanoparticle ink has better conductivity. Selecting a particle size range of 20nm to 2μm can achieve a good balance in terms of cost, dispersibility, optical properties, filling effect and rheological properties. When the particle size is too small (<20nm), the nanoparticles are easy to agglomerate, the preparation process is complex and difficult, and the cost is high; when the particle size is too large (>2μm), the particle size of the particles becomes larger, the specific surface area decreases, the reduction efficiency decreases, and it may affect the rheological properties of the ink and the coating quality, making it difficult to apply to high-precision application scenarios.

[0018] On the basis of the above technical solution, preferably, in the composite ink, by mass percentage, the copper ion ink is 20%-70%, the copper oxide particles are 20%-60% and the polyvinyl pyrrolidone is 10%-20%.

[0019] Copper oxide particles are one of the main sources of copper in ink. A higher content of copper oxide particles is beneficial to increasing the copper content in the ink and reducing the volume shrinkage and mass loss during laser induction. However, too high a content leads to enhanced interaction between particles, increased ink viscosity, and poor fluidity, which is not conducive to obtaining a uniform and smooth coating by printing.

[0020] Polyvinyl pyrrolidone acts as a dispersant and reducing agent for copper oxide in the ink. Too high a content of polyvinyl pyrrolidone will cause a decrease in the copper content and a waste of polyvinyl pyrrolidone, while too low a content of polyvinyl pyrrolidone will cause the dispersion of copper oxide nanoparticles to deteriorate, easily causing particle agglomeration and insufficient laser-induced reduction.

[0021] The copper ion ink content is one of the sources of copper in the ink, which determines the copper content. At the same time, as the main liquid phase component in the ink, it determines the fluidity of the ink. Too low copper ion ink content causes the ink fluidity to deteriorate. At the same time, because the proportion of copper in copper ion ink is much lower than that of copper oxide particles, too high copper ion ink content will cause the copper content in the ink to decrease.

[0022] In a second aspect, the present invention provides a composite ink, which is prepared by using any of the preparation methods described above.

[0023] In a third aspect, the present invention provides an application of a composite ink, wherein the composite ink is used to prepare a selective copper metallization product, and the preparation method comprises the following steps:

[0024] A1. The composite ink is uniformly formed into a film on the target substrate by using solution forming technology, and pre-baking is performed to remove the organic solvent, and the pre-baking parameters are 60-80°C, 5-15min; the solution forming technology includes: spin coating, drop coating, dip coating, inkjet printing, screen printing and other solution forming methods; the substrate material can be silicon wafer, quartz wafer, sapphire wafer, polyimide, soda-lime glass, etc.;

[0025] A2. Use a laser induction method to perform patterned direct writing on the ink film to induce decomposition, reduction, and sintering of the ink, followed by cleaning and development to obtain a patterned selective copper metallization product. For heat-sensitive substrates, the product after cleaning and development can be used directly. For high-temperature resistant substrates, the present invention can further improve the chemical composition, porosity, and conductivity of the product through post-step heat treatment. Among them, the post-step heat treatment specifically includes: post-step heat treatment of the metallic copper product obtained after cleaning and development in a specific atmosphere environment; the special atmosphere environment is argon, nitrogen, hydrogen, argon-hydrogen mixed gas, nitrogen-hydrogen mixed gas and other atmosphere environments; the heat treatment temperature is 300-400°C, and the heat treatment time is ≥10min.

[0026] The copper ion and copper oxide composite ink system proposed in the present invention fills the gaps between copper oxide particles through copper ion reduction, nucleation, growth and laser-induced melting effect; the copper element content is greatly increased by the introduction of copper oxide particles, and finally the preparation of a metallic copper product with high line height, low porosity and high conductivity is achieved. The uniform coating and film formation of the ink are achieved by solution forming technology, and then the conductive copper metallization pattern is directly written on the ink film by utilizing the laser-induced selective reduction and sintering effect. This method is simple to operate, does not require a mask, and can achieve rapid and flexible preparation of copper metallization patterns with high resolution and selectivity. At the same time, the present invention can also directly form a pattern by patterned printing means, and directly scan the pattern during laser-induced reduction, thereby reducing ink waste. The present invention has broad application prospects in the fields of flexible electronics, printed electronics, etc.

[0027] On the basis of the above technical scheme, preferably, in step A2, the parameters of the laser induction method specifically include: the laser center wavelength is 1000nm~1100nm near-infrared band, the laser pulse width is ≥100fs, the repetition frequency is ≥500KHz, the laser power is ≥50mW, and the scanning speed is ≥1mm / s. Among them, too small laser pulse width and too small laser repetition frequency will lead to too high laser single pulse energy and too large peak power, so that under the action of multiple laser pulses, the generated copper product is etched, and low pulse width and low repetition frequency are not conducive to temperature accumulation at the laser focus and decomposition of ink. The scanning speed below 1mm / s is too inefficient and has no practical significance, and too low laser power is not enough to achieve good laser induced reduction sintering at a scanning speed of ≥1mm / s.

[0028] The bandgap width of copper oxide in the composite ink system of the present invention is about 1.2eV, and the corresponding photon energy matches the near-infrared laser with a wavelength of 1000nm to 1100nm. This band structure matching can significantly improve the absorption efficiency of the ink to near-infrared light, promote the transition of electrons between the valence band and the conduction band, thereby accelerating the generation of photogenerated carriers and the photothermal conversion process, improving the efficiency of laser-induced reduction and sintering, reducing light energy loss, and reducing energy penetration to the substrate to avoid substrate damage.

[0029] The composite ink and process method for laser-induced selective copper metallization of the present invention have the following beneficial effects compared with the prior art:

[0030] (1) The copper ion and copper oxide composite ink system proposed in the present invention fills the gaps between copper oxide particles through copper ion reduction, nucleation, growth and laser-induced melting effect; the copper content is greatly increased by the introduction of copper oxide particles, and finally the preparation of a metallic copper product with high line height, low porosity and high conductivity is achieved;

[0031] (2) Primary amine complexing agents with long alkyl chains are used to regulate the reduction nucleation process of copper ions, making their particle size smaller and more uniform, thereby facilitating melting under laser action and enhancing their filling effect on pores;

[0032] (3) Copper oxide is used as solid phase particles to introduce into copper ion ink, which has the advantages of low cost and easy storage and transportation compared with copper nanoparticles;

[0033] (4) Since the copper oxide bandgap (~1.2 eV) matches the wavelength of the mainstream near-infrared laser light source (1000nm~1100nm), the composite ink system of the present invention has strong absorption in this wavelength range, which is beneficial to further improve the energy coupling efficiency between laser and matter, improve processing efficiency, and avoid damage to the substrate;

[0034] (5) The present invention optimizes the reducing agent and solvent system in the existing ink, avoids the use of high-boiling point solvents and reducing agents, removes volatile solvents through a pre-baking process, alleviates the micro-explosion phenomenon at the focal position during laser processing, and greatly reduces the porosity in the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 The invention provides a preparation process of the composite ink for laser-induced selective copper metallization and the copper metallization product;

[0037] Figure 2 This is a diagram of the copper metallization product prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] This embodiment provides a composite ink and a process method for laser-induced selective copper metallization, which specifically includes the following steps:

[0041] (1) copper sulfate is prepared into a 1 mol / L solution A, and anhydrous formic acid is prepared into a 2 mol / L solution B; 20 wt % sodium hydroxide is used to adjust the pH value of solution B to 6-8; solution A and solution B are mixed in equal volumes and stirred for 6 hours; the mixed solution is concentrated by heating evaporation, and the solvent is removed by filtering and vacuum drying to obtain solid copper formate;

[0042] (2) 2 mmol of copper formate and 4 mmol of isopropylamine were added as a complexing agent to 1 ml of isopropanol, followed by magnetic stirring for 12 h (rotation speed of 800 rpm) to obtain copper ion ink; 1.2 g of micron-sized spherical copper oxide particles (particle size of 2 μm) and 0.5 g of polyvinyl pyrrolidone were added, and a composite ink was obtained by water bath ultrasound for 30 min.

[0043] (3) The ink was evenly coated on a soda-lime glass substrate by spin coating and pre-baked at a spin coating speed of 2000 rpm for 30 s and a pre-baking temperature of 80° C. for 10 min.

[0044] (4) Selective metallization of the ink film was induced by an infrared picosecond laser at 1064 nm, a pulse width of 10 ps, ​​and a repetition frequency of 2 MHz, with a laser power of 2 W and a scanning speed of 1 mm / s. After processing, the substrate was placed in anhydrous ethanol for development for 30 min, then rinsed with deionized water for 5 s, and dried with argon. The obtained product was placed in a 95% and 5% argon-hydrogen mixture for a post-step heat treatment at 400°C for 30 min to obtain a patterned selective copper metallization product.

[0045] Example 2

[0046] This embodiment provides a composite ink and process method for laser-induced selective copper metallization. The specific preparation method is the same as that of Embodiment 1, except that the complexing agent in step (2) is octylamine.

[0047] Example 3

[0048] This embodiment provides a composite ink and process for laser-induced selective copper metallization, the preparation method is as follows Figure 1 The specific preparation method is the same as that of Example 2, except that the copper oxide particles in step (2) are nanoscale spherical particles with a particle size of 100 nm. The copper metallization product prepared is as follows: Figure 2 shown.

[0049] Example 4

[0050] This embodiment provides a composite ink and a process method for laser-induced selective copper metallization, which specifically includes the following steps:

[0051] (1) preparing a 0.5 mol / L solution A with copper sulfate and a 1 mol / L solution B with anhydrous formic acid; adjusting the pH value of solution B to 6-8 with 20 wt % sodium hydroxide; mixing solution A and solution B in equal volumes, stirring at 25° C. for 8 h; concentrating the mixed solution by heating and evaporation, and removing the solvent by filtering and vacuum drying to obtain solid copper formate;

[0052] (2) 2 mmol of copper formate and 3 mmol of octylamine were added as a complexing agent to 2 ml of isopropanol, followed by magnetic stirring for 12 h (rotation speed of 800 rpm) to obtain 2.27 g of copper ion ink; 6.81 g of nano-spherical copper oxide particles (particle size of 20 nm) and 2.27 g of polyvinyl pyrrolidone were added, and a composite ink was obtained by water bath ultrasound for 30 min. In the composite ink, copper ion ink accounts for 20 wt%, copper oxide particles account for 60 wt%, and polyvinyl pyrrolidone accounts for 20 wt%.

[0053] (3) The ink was evenly coated on a soda-lime glass substrate by spin coating and pre-baked at a spin coating speed of 2000 rpm for 30 s and a pre-baking temperature of 60° C. for 5 min.

[0054] (4) Infrared picosecond laser induced ink film selective metallization with a laser power of 500 mW and a scanning speed of 3 mm / s was used to induce the ink film with a laser power of 1030 nm, a pulse width of 400 fs and a repetition frequency of 500 KHz. After processing, the substrate was placed in anhydrous ethanol for development for 30 min, then rinsed with deionized water for 5 s and dried with argon. The obtained product was placed in a mixture of argon and hydrogen with a volume percentage of 95% and 5% for post-step heat treatment at 300 ° C for 10 min to obtain a patterned selective copper metallization product.

[0055] Example 5

[0056] This embodiment provides a composite ink and a process method for laser-induced selective copper metallization, which specifically includes the following steps:

[0057] (1) preparing a 0.8 mol / L solution A with cupric chloride and a 1.5 mol / L solution B with anhydrous formic acid; adjusting the pH value of solution B to 6-8 with 20 wt % sodium hydroxide; mixing solution A and solution B in equal volumes, stirring at 25° C. for 12 h; concentrating the mixed solution by heating and evaporation, and removing the solvent by filtering and vacuum drying to obtain solid copper formate;

[0058] (2) Take 2mmol copper formate and 5mmol hexylamine as a complexing agent and add them to 0.4ml isopropanol, followed by magnetic stirring for 12h (rotation speed is 800rpm) to obtain 1.13g copper ion ink; add 0.32g nano-spherical copper oxide particles (particle size is 200nm) and 0.16g polyvinyl pyrrolidone, and use water bath ultrasound for 30min to obtain a composite ink, in which copper ion ink accounts for 70wt%, copper oxide particles account for 20wt%, and polyvinyl pyrrolidone accounts for 10wt%.

[0059] (3) The ink was evenly coated on a soda-lime glass substrate by spin coating and pre-baked at a spin coating speed of 2000 rpm for 30 s and a pre-baking temperature of 70° C. for 15 min.

[0060] (4) Infrared picosecond laser induced ink film selective metallization was performed using a 1030nm, 10ps pulse width, and 2MHz repetition frequency laser. The laser power was 2W and the scanning speed was 1mm / s. After processing, the substrate was placed in anhydrous ethanol for development for 30min, then rinsed with deionized water for 5s and dried with argon. The obtained product was placed in a 95% by volume, 5% argon and hydrogen mixed gas for a post-step heat treatment at 350°C for 30min to obtain a patterned selective copper metallization product.

[0061] Example 6

[0062] The present embodiment provides a composite ink and process method for laser-induced selective copper metallization. The specific preparation method is the same as that of Example 3, except that: in step (1), copper nitrate is prepared into a 1 mol / L solution A, and glyoxylic acid is prepared into a 1 mol / L solution B; in step (2), the complexing agent is nonylamine, and the organic solvent is ethanol.

[0063] Example 7

[0064] This embodiment provides a composite ink and process method for laser-induced selective copper metallization. The specific preparation method is the same as that of Example 3, except that: in step (1), copper chloride is prepared into 0.5 mol / L solution A; in step (2), the complexing agent is heptylamine and the organic solvent is ethanol.

[0065] Example 8

[0066] This embodiment provides a composite ink and process method for laser-induced selective copper metallization. The specific preparation method is the same as that of Example 3, except that the copper oxide particles in step (2) are nano-scale flaky particles.

[0067] Example 9

[0068] This embodiment provides a composite ink and process method for laser-induced selective copper metallization. The specific preparation method is the same as that of Example 3, except that the copper oxide particles in step (2) are nano-scale rod-shaped particles.

[0069] Example 10

[0070] This embodiment provides a composite ink and process method for laser-induced selective copper metallization. The specific preparation method is the same as that of Example 3, except that: the amount of copper oxide particles added in step (2) is 2.5 g, that is, the amount of copper oxide particles added accounts for 80%.

[0071] Embodiment 11

[0072] This embodiment provides a composite ink and process method for laser-induced selective copper metallization. The specific preparation method is the same as that of Example 3, except that: the amount of copper oxide particles added in step (2) is 0.32 g, that is, the amount of copper oxide particles added accounts for 10%.

[0073] Example 12

[0074] This embodiment provides a composite ink and process method for laser-induced selective copper metallization. The specific preparation method is the same as that of Example 3, except that in step (2), the amount of copper formate added is 2 mmol, and the amount of octylamine added is 8 mmol.

[0075] Embodiment 13

[0076] This embodiment provides a composite ink and process method for laser-induced selective copper metallization, which is different from Embodiment 3 in that there is no post-heat treatment step. This embodiment is compatible with heat-sensitive substrates.

[0077] Comparative Example 1

[0078] This comparative example provides a pure copper ion ink and a process method, which specifically comprises the following steps:

[0079] (1) copper sulfate is prepared into a 1 mol / L solution A, and anhydrous formic acid is prepared into a 2 mol / L solution B; 20 wt % sodium hydroxide is used to adjust the pH value of solution B to 6-8; solution A and solution B are mixed in equal volumes and stirred for 6 hours; the mixed solution is concentrated by heating evaporation, and the solvent is removed by filtering and vacuum drying to obtain solid copper formate;

[0080] (2) 2 mmol of copper formate, 2 mmol of 2-amino-2-methyl-1-propanol and 2 mmol of octylamine were added to 1 ml of isopropanol as a complexing agent, and then magnetic stirring was performed for 12 hours (at a speed of 800 rpm) to prepare a copper ion ink solution. In this comparative example, the metal salt contains a reducing formic acid group, so no additional reducing agent is required;

[0081] (3) The ink was evenly coated on a soda-lime glass substrate by spin coating and pre-baked at a spin coating speed of 3000 rpm for 30 s and a pre-baking temperature of 80° C. for 10 min.

[0082] (4) A near-infrared femtosecond laser with a pulse width of 1030 nm, a pulse width of 100 fs, and a repetition frequency of 80 MHz was used to induce selective metallization of the ink film. The laser power was 70 mW and the scanning speed was 1 mm / s. After the processing was completed, the substrate was placed in anhydrous ethanol for development for 30 min, then rinsed with deionized water for 5 s and dried with argon gas. The obtained product was placed in a 95% and 5% argon-hydrogen mixture for a post-step heat treatment at 400°C for 30 min to obtain a patterned selective copper metallization product.

[0083] Comparative Example 2

[0084] This comparative example provides a copper oxide nanoparticle ink and a process method, and the specific operation steps are as follows:

[0085] (1) Spherical copper oxide nanoparticles (50 wt%) (average particle size 20-30 nm) were prepared by using polyvinyl pyrrolidone (16 wt%) as a dispersant and ethylene glycol (34 wt%) as a solvent and a reducing agent, and then dispersed in a water bath for 30 min to obtain a copper oxide nanoparticle ink;

[0086] (2) The ink was evenly coated on a soda-lime glass substrate by spin coating and pre-baked at a spin coating speed of 1500 rpm for 30 s and a pre-baking temperature of 80° C. for 10 min.

[0087] (3) A femtosecond laser with a pulse width of 100 fs and a repetition frequency of 80 MHz was used to induce selective metallization of the ink film, with a laser power of 50 mW and a scanning speed of 1 mm / s. After processing, the substrate was placed in anhydrous ethanol for development for 30 min, then rinsed with deionized water for 5 s and dried with argon. The obtained product was placed in a 95% and 5% argon-hydrogen mixture for a post-step heat treatment at 400°C for 30 min to obtain a patterned selective copper metallization product.

[0088] Comparative Example 3

[0089] This comparative example provides a composite ink and process method for laser-induced selective copper metallization. The specific preparation method is the same as that of Example 3, except that ethylene glycol is used in step (2) to replace isopropyl alcohol as the solvent of the composite ink system.

[0090] Performance Testing

[0091] 1. Line height test

[0092] The line heights of the copper metallization products prepared in Examples 1-12 and Comparative Examples 1-3 were measured using a DektakXT probe-type surface profiler.

[0093] 2. Conductivity function test

[0094] The resistance of the copper metallization products prepared in the above Examples 1 to 12 and Comparative Examples 1 to 3 was detected by a semiconductor analyzer B1500A based on a four-probe analysis method, and the sample geometry information was obtained based on a microscope and a DektakXT probe surface profiler, and the sample resistivity was calculated.

[0095] 3. Porosity measurement

[0096] The surfaces of the copper metallization products prepared in Examples 1 to 12 and Comparative Examples 1 to 3 were imaged and photographed using a Nova NanoSEM 450FP2053 / 45 thermal field emission scanning electron microscope, and the porosity of the test images was analyzed based on ImageJ software.

[0097] 4. Absorption rate test

[0098] The spin coating method was used to spin-coat a 20 mm × 20 mm × 1 mm JGS2 quartz substrate, and the ink films of Examples 1 to 12 and Comparative Examples 1 to 3 were obtained after pre-baking. The film thickness was tested based on the contact step profiler DektakXT, and the film absorbance was tested by the SolidSpec-3700 UV-visible near-infrared spectrophotometer. The absorbance was normalized to 10 microns according to the film thickness and converted into absorptivity according to the defined formula.

[0099] The test results are shown in Table 1.

[0100] Table 1

[0101]

[0102] As shown in Table 1, the copper metal structure line height prepared by using copper ion and copper nanoparticle composite ink in Examples 3-8 is significantly improved compared with the copper ion ink in Comparative Example 1, and its porosity is significantly reduced compared with the copper oxide nanoparticle ink in Comparative Example 2. Compared with Example 3, Comparative Example 3 replaces ethylene glycol with a volatile solvent, which is beneficial to reduce porosity and improve resistivity. Compared with Comparative Example 1, the optical absorbance at 1064nm of Examples 3 to 8 is greatly improved. Compared with Examples 1-3, the chain length of the primary amine and the particle size of copper oxide have an important influence on the resistivity and pore size of the product. Long alkyl chains and nanometer-scale particle sizes are more conducive to achieving high conductivity and high density products. Comparing Examples 8 and 9 with Example 3, it is shown that the morphology of the copper oxide particles will also affect the conductivity of the product. Comparing Examples 10 and 11 with Example 3, it is shown that the amount of copper oxide particles added has a significant effect on the line height, resistivity, porosity and light absorptivity of the product. Comparing Example 12 with Example 3, it is shown that the ratio of the self-reducing copper salt and the complexing agent of the present application is more conducive to high conductivity and high density products.

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An application of a composite ink for laser-induced selective copper metallization, characterized in that: The preparation method of the composite ink comprises the following steps: S1. Mixing a self-reducible copper salt, a primary amine and a volatile organic solvent to prepare a copper ion ink, wherein the primary amine comprises one or more long alkyl primary amines with an alkyl chain length of ≥5, and the volatile organic solvent is a solvent with a boiling point of ≤85°C; S2, mixing the copper ion ink, copper oxide particles and polyvinyl pyrrolidone to prepare a composite ink; The self-reducible copper salt includes copper formate or copper glyoxylate, and the long alkyl primary amine includes one or more of octylamine, nonylamine, heptylamine, and hexylamine; The molar ratio of the self-reducible copper salt to the long alkyl primary amine is 1:1.5-2.5; the copper oxide particles are spherical and / or flaky; The composite ink is used to prepare a selective copper metallization product, and the preparation method comprises the following steps: A1. The composite ink is uniformly formed into a film on the target substrate by using solution forming technology, and pre-baking is performed to remove the organic solvent. The pre-baking parameters are 60-80° C. and 5-15 min. A2. Using a laser induction method, patterned direct writing is performed on the ink film to induce decomposition, reduction, and sintering of the ink, followed by cleaning, development, and post-step heat treatment to obtain a patterned selective copper metallization product; the substrate material is any one of a silicon wafer, a quartz wafer, a sapphire wafer, a polyimide, and a soda-lime glass; The heat treatment temperature is 300~400℃, and the heat treatment time is ≥10 min; The parameters of the laser induction method specifically include: the laser center wavelength is in the near-infrared band of 1000 nm to 1100 nm, the laser pulse width is ≥100 fs, the repetition frequency is ≥500 kHz, the laser power is ≥50 mW, and the scanning speed is ≥1 mm / s; The copper ion concentration in the copper ion ink is 1-5 mol / L; The preparation method of the self-reducible copper salt comprises: mixing a copper metal salt solution and a reducing carboxylic acid solution, reacting at 24-28° C. for 6-12 hours, removing the solvent to obtain the self-reducible copper salt, wherein the pH value of the reducing carboxylic acid solution is 6-8; The concentration of the copper metal salt solution is 0.5-1 mol / L, and the copper metal salt solution includes one or more of a copper sulfate solution, a copper nitrate solution, and a copper chloride solution; the concentration of the reducing carboxylic acid solution is 1-2 mol / L, and when the self-reducing copper salt is copper formate, the reducing carboxylic acid solution is a formic acid solution; when the self-reducing copper salt is copper glyoxylate, the reducing carboxylic acid solution is a glyoxylic acid solution; The particle size of the copper oxide particles is 20 nm to 200 nm; In step S2, in the composite ink, by mass percentage, the copper ion ink accounts for 20%-70%, the copper oxide particles account for 20%-60% and the polyvinyl pyrrolidone accounts for 10%-20%.

2. The use of a composite ink for laser-induced selective copper metallization according to claim 1, characterized in that: The organic solvent includes one of methanol, ethanol and isopropanol.

Citation Information

Patent Citations

  • Liquid composition, copper metal film, conductive wiring line, and method for producing copper metal film

    CN104185880A

  • Copper formate complex, method for producing copper particle and method for producing circuit board

    JP2008013466A

  • Method for Reducing Thin Films on Low Temperature Substrates

    US20180103546A1